In situ simulation training strengthened bachelor of nursing students' experienced learning and development process- a qualitative study - Karina Karlsen; Carina Nygård; Lisbeth Gaustad Johansen; Edith Roth Gjevjon (BMC, 2024)
Abstract Background In advanced clinical learning labs on campus, high-fidelity simulation has become an essential educational approach in the Bachelor of Nursing Education programme. However, simulation while in clinical placement, in situ, is rarely used in Bachelor of Nursing Education. The aim of the present study was to explore how in situ simulation training at a surgical hospital ward, according to Bachelor of Nursing students, influenced their learning and development process. Methods A qualitative descriptive study was conducted. Data were collected through individual interviews with a sample of 21 s-year Bachelor of Nursing students who completed 40 in situ simulations during their eight-week clinical placement at a Norwegian University Hospital. Data were analysed using inductive content analysis. Results The data analysis generated six subcategories constituting two descriptive categories: building professional confidence and internalising nursing knowledge. Although the students found in situ simulation stressful and uncomfortable for being assessed by student peers, the teacher and preceptor, the process of managing clinical situations in simulation helped build professional confidence. What the students had learned in the simulation was directly transferable to real clinical situations because they were in the hospital setting. The simulation sessions enabled them to connect theoretical knowledge and clinical skills. They could test their skills in a safe environment, performing procedures that made them aware of how their knowledge could be used in real life. Conclusion According to the Bachelor of Nursing students' own experiences, in situ simulation supported the students' learning process, connected theory and practice and contributed to developing confidence in the performance of clinical skills. Including simulation in clinical practice could prove to be an effective way of teaching and learning clinical skills in nursing regarding resources and learning outcomes.